Effects of manual motor and cognitive training on functionality and cognition of institutionalized elderly people. - Simionatto, Jaqueline; Duarte Fantesia Costa Cruz, Arthur; Paula Souza Malta Campos, Ana; Aparecida Moisés Caetano Bottini, Dayane; Hotta Ansai, Juliana; Beatriz Gomes de Souza Pegorare, Ana; Rosa Miziara Barbosa, Suzi (O Mundo da Saúde, 2020)
This study aimed to verify the effects of manual and cognitive motor training on the functionality and cognition of institutionalized elderly people. 26 institutionalized elderly participated in the study and were divided into two groups at random: Intervention Group (IG) (n=13) and Control Group (CG) (n=13). In the IG, 17 interventions were performed with games that worked on cognitive functions and playful-collective activities that stimulated memory, social interaction, and manual motor skills, whereas the CG did not. To assess functionality, the Katz Scale and the Barthel Index were used. For cognitive evaluation, the Mini Mental State Examination (MMSE), the Clock-drawing Test, and the Verbal Fluency Test were used. In the statistical analysis, the difference between the final and initial scores (delta), the t test for comparison between groups, and a significance level of 5% were used. As a result, the IG was composed mainly of women (61.54%) and had a mean age of 78.07 years. In the CG, there were more men (61.54%), with a mean age of 74.84 years. There was a significant improvement in the IG in the scores of the Katz Scale, MMSE and Verbal Fluency Test, compared to the CG. The use of activities that assist in independence, cognition, memory, and socialization are necessary to maintain and/or improve functionality, contributing to guarantee the quality of life of the elderly. Thus, this study contributes to the practice of sensorymotor and cognitive stimulation in long-term care facilities for the elderly, acting in a complementary way to public health policies for the elderly.